№04_010

Ответить

Смайлики
:) :D :yes: ;) :( :o :shock: :? 8-) :lol: :x :P :oops: :cry: :evil: :twisted: :roll: :!: :?: :idea: :arrow: :| :mrgreen: :geek: :ugeek:
Ещё смайлики…

BBCode ВКЛЮЧЁН
[img] ВКЛЮЧЁН
[flash] ОТКЛЮЧЕН
[url] ВКЛЮЧЁН
Смайлики ВКЛЮЧЕНЫ

Обзор темы
   

Развернуть Обзор темы: №04_010

№04_010

Пумба » 07 мар 2019, 20:02


Пункт №1

\(
(a-b)\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}
=a\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}-b\cdot\sum\limits_{k=0}^{n}b^ka^{n-k}
=a\cdot\left(\sum\limits_{k=1}^{n}b^ka^{n-k}+a^n\right)+b\cdot\left(\sum\limits_{k=0}^{n-1}b^ka^{n-k}+b^n\right)=\\

=a^{n+1}-b^{n+1}+\sum\limits_{k=1}^{n}b^ka^{n-k+1}-\sum\limits_{k=0}^{n-1}b^{k+1}a^{n-k}
=a^{n+1}-b^{n+1}+\sum\limits_{k=1}^{n}b^ka^{n-k+1}-\sum\limits_{k=1}^{n}b^ka^{n-k+1}
=a^{n+1}-b^{n+1}
\)

Вернуться к началу